Groups : process and practice - Corey, Marianne Schneider, 1942-; Corey, Gerald; Corey, Cindy (Cindy C.); Brooks/Cole Publishing Company (Belmont, CA : Brooks/Cole, Cengage Learning, 2014)
"This book outlines the basic issues and key concepts of group process and shows how group leaders can apply these concepts in working with a variety of groups. In many ways this is a 'how-to' book, but it is also a book about the 'why' of group leadership. For the ninth edition, each chapter has been carefully reviewed and updated to present the current thinking and trends in practice." --p. xxi
Contents note continued: In-Class Activities. Coleader Issues as the Group Ends -- Follow-Up -- Postgroup Sessions -- Points to Remember -- Final Stage Characteristics -- Member Functions -- Leader Functions -- Exercises -- Final Stage of a Group -- Questions for Discussion -- Guide to Groups in Action: Evolution and Challenges DVD and Workbook -- ch. 11 Application of Group Process to Schools and Community Agency Settings -- ch. 10 Groups in School Settings -- Introduction -- Group Counseling in the School Setting -- Guidelines for Group Work With Children and Adolescents -- Developing a Sound Proposal -- Legal Considerations -- Practical Considerations -- Strategies in the Group -- Play Therapy in Group Work With Children and Adolescents -- Personal and Professional Qualifications -- Getting Support for School Counseling Groups -- Group Proposal: A School Counseling Group for 6- to II-Year-Olds-- Group Proposal: A Group for Elementary School Children of Divorce and Changing Families -- Group Proposal: A Group for Children Who Have Been Abused -- Developmental Themes of Adolescence -- Sources of Stress During Adolescence -- Developmental Group Counseling With Adolescents -- Issues and Challenges in Leading Adolescent Groups -- Establishing Trust -- KnowYour Comfort Zone With Self-Disclosure -- Group Proposal: Teens Making a Change (T-MAC): A Group for Preventing Teen Delinquency -- Helping Adolescents Deal With Anger and Conflict -- Group Proposal: A High School Anger Management Group -- Groups in College Counseling Centers -- Common Topics in College Groups -- Some Groups for College Students -- Points to Remember -- Groups in School Settings -- Exercises -- In-Class Activities -- ch. 11 Groups in Community Settings -- Introduction -- Group Work With Women -- Group Proposal: A Women's Support Group for Survivors of Incest-- Group Work With Men -- Group Proposal: A Men's Group in a Community Agency -- Group Treatment of Domestic Violence Offenders -- Group Proposal: An Involuntary Domestic Violence Group -- Group Treatment of Sex Offenders -- Group Proposal: A Group for the Treatment of Sex Offenders -- AIDS Crisis as a Challenge for Group Workers -- How Groups Can Help -- Educational Focus in HIV/AIDS Groups -- Group Proposal: An HIV/AIDS Support Group -- Group Work With Older Adults -- Attitudes, Knowledge, and Skills of Leaders -- Preparing Yourself to Work With Older Adults -- Practical and Professional Considerations for Group Work With Older Adults -- Guidelines for the Group Process -- Working With Healthy Aging People in Groups -- Group Proposal: A Successful Aging Group -- Therapeutic Value of Grief Work in Groups -- Group Proposal: An Older Adult Bereavement Group -- Group Proposal: A Group Treatment Program for Institutionalized Older Adults -- Therapeutic Value of Touch -- Points to Remember -- Groups in Community Settings -- Exercises -- In-Class Activities.
Includes bibliographical references (pages 425-437) and indexes.
Keywords: Group psychotherapy; Group counseling; Group relations training; Psychotherapy, Group; Group Processes; Counseling; Group counseling; Group psychotherapy; Group relations training